Leaf-stomata-inspired packaging nanofibers with humidity-triggered thymol release based on thymol/EVOH coaxial electrospinning. (December 2022) - Zhang, Wenmin; Liu, Rong; Sun, Xiaoli; An, Heng; Min, Tiantian; Zhu, Zhu; Wen, Yongqiang
Graphical abstract: Highlights: An innovative nanofiber film via coaxial electrospinning using thymol as core layer and EVOH as shell layer was developed. The hydrophilic EVOH shell as smart "switch" achieved controlled release of thymol triggered by the relative humidity. Thymol/EVOH nanofibers had excellent antimicrobial and biocompatibility. The humidity-responsive packaging film had a great potential for food preservation. Abstract: Active packaging systems that are sustainable and capable of delivering antimicrobial agents intelligently are in demand in food industry. In this work, an extremely simple strategy inspired by leaf stomata was introduced to smartly trigger thymol release at different relative humidity using EVOH as the "stomata". Thymol was encapsulated into ethylene vinyl alcohol copolymer (EVOH) to form core–shell nanofibers (thymol/EVOH) via coaxial electrospinning. The core–shell structure of the nanofiber was confirmed by transmission electron microscopy. Thymol release could be triggered by the relative humidity (RH), and nanofibers released more thymol at 90% RH than at 30% RH. In addition, this functionalized nanofibers showed excellent antibacterial activity in vitro against Escherichia coli and Staphylococcus aureus and performed good biocompatibility. The nanofiber film was also applied to fruit preservation, and was found to extend the strawberries shelf-life. Sensory analysis also showed that the strawberries flavor treated by thymol/EVOH nanofibers presented high acceptability. The work will provide an innovative approach to design packaging film.